VISUALISASI 3 DIMENSI KAMPUS MUGAS UNIVERSITAS STIKUBANK (UNISBANK) SEMARANG 3 DIMENSIONAL VISUALIZATION UNIVERSITY CAMPUS MUGAS STIKUBANK ( UNISBANK ) SEMARANG (Information Technology and Telematics, 2015)
Abstract – The development of technology in today's world has been extraordinary rapid, almost every sector of the industry and the educational use of technology, especially computers. So much that race - the race to make something interesting and interactive. One way is to menvisualkan into 3-dimensional object. 3-dimensional visualization Stikubank University aims as one of the media campaign to introduce UNISBANK to the general public. Because in today's world people are more interested in something unique or interesting video beruupa also compared with a reading that is so long. Therefore, this makes the visualization penulismembuat media campaign interesting and interactive to be enjoyed by the general public and also to attract people to join into one part of the UNISBANK. The results of this study, namely, in the form of flash applications, such as company profile of UNISBANK to view the company profile UNISBANK be interesting and interactive as a good media campaign. Keywords : 3D visualization , University Stikubank